Apple rootstocks: past, present and future - Denardi, Frederico (2017)
Abstract: The global evolution of the use of apple rootstocks can be classified on three distinct phases: a) Own rooted and seedlings: involving a millennial period along of it the emphasis was on propagation ability by seeds and induction of vigor to the scion; b) Clonal rootstocks: developed with emphasis on propagation ability, grafting compatibility, good root anchorage, good ability to control scion vigor and resistance to woolly apple aphid; c) Clonal rootstocks with attributes of universal interest: in addition to some attributes peculiar to the previous used rootstocks, good ability on vigor control of the scion, induction of high precocity and high productivity of good fruit quality are attributes of universal interest from the rootstocks developed after the 1970’s. Besides, several rootstocks developed in this presented have the resistance to biotic factors as complementary attributes, such as collar rot and root rot, woolly apple aphid and fire blight.